Ritual notes; a comprehensive guide to the rites and ceremonies of the Book of common prayer of the English Church, interpreted in accordance with the latest revisions of the Western use - Lamburn, E C R (London W. Knott, 1964)
This work originated as a series of notes in the kalendar The Order of Divine Service in the years from 1887 onwards, and first appeared in book form in 1894. The present edition is the eleventh; and this alone is sufficient testimony to its acceptability as a reliable and authoritative guide for Anglicans who wish to order their services in accordance with contemporary 'Western Use'. (from the dust jacket).
Keywords: Church of England. -- Book of common prayer. Book of common prayer (Church of England)